A kind of high wear-resistant ceramic tile and preparation method thereof

By adding 60 to 120 mesh zircon to the protective glaze slurry of marble tiles and controlling its particle size and addition ratio, the problem of poor wear resistance on the glaze surface of the tiles is solved, and the effect of high wear resistance, anti-slip and uniform light sense is achieved.

CN119431014BActive Publication Date: 2025-04-29FOSHAN CITY GANI CERAMICS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510038189.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-29
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The glaze surface of existing marble tiles is poorly abrasion-resistant, and scratches are prone to occur during use, affecting gloss and surface effect.

Method used

Mix zircon 60 to 120 mesh into the protective glaze slurry, and physically blend it to improve the wear resistance and anti-slip properties of the glaze surface while maintaining the light and transparency of the glaze surface.

Benefits of technology

It significantly improves the wear resistance and anti-slip properties of the glaze surface of the ceramic tile, prevents the glaze surface from whitening, ensures light sense and transparency, and improves overall strength and comprehensive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the field of building ceramics, and in particular to a highly wear-resistant ceramic tile and a preparation method thereof, wherein the highly wear-resistant ceramic tile comprises a body layer, a surface glaze layer, a decorative layer and a protective glaze layer, wherein the raw materials for preparing the protective glaze layer comprise a protective glaze slurry and zircon, wherein the particle size of the zircon is 60 to 120 meshes, and the addition ratio of the zircon is 20% to 40% based on the total amount of the protective glaze slurry. The present invention improves the overall strength of the glaze surface after firing by physically blending 60 to 120 meshes of zircon in the protective glaze slurry, so that the ceramic tile has high wear resistance, and at the same time, by adjusting the particle size and addition ratio of the zircon, the glaze surface can be effectively prevented from whitening, thereby ensuring the light perception and transparency of the protective glaze layer, and not affecting the color development of the decorative layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building ceramics, and in particular to a high-wear-resistant ceramic tile and a preparation method thereof. Background Art

[0002] Marble tiles are widely favored by consumers because of their texture, color and texture that can achieve the realistic effect of natural marble, and the decorative effect is far better than natural stone. However, the glaze surface of existing marble tiles has the disadvantage of poor wear resistance, which will cause scratches on the originally bright surface during use, affecting the glossiness and surface effect.

[0003] Therefore, how to improve the wear resistance of marble tiles is an urgent problem to be solved in the ceramic industry. Summary of the invention

[0004] The main purpose of the present invention is to provide a highly wear-resistant ceramic tile to solve the technical problem that the glaze surface of the marble ceramic tile in the prior art has poor wear resistance.

[0005] To achieve the above-mentioned purpose, the present invention proposes a high wear-resistant ceramic tile, which includes a body layer, a surface glaze layer, a decorative layer and a protective glaze layer. The raw materials for preparing the protective glaze layer include a protective glaze slurry and zircon. The particle size of the zircon is 60 to 120 meshes. Based on the total amount of the protective glaze slurry, the addition ratio of the zircon is 20% to 40%.

[0006] The present invention mixes 60-120 mesh zircon into the protective glaze slurry, so that the glaze surface after firing can not only improve the overall strength and have high wear resistance, but also effectively prevent the glaze surface from whitening by adjusting the particle size and addition ratio of the zircon, thereby ensuring the lightness and transparency of the protective glaze layer.

[0007] Preferably, the particle size of the zircon is 80-100 mesh.

[0008] Preferably, the addition ratio of zircon is 30% based on the total amount of the protective glaze slurry.

[0009] Adjust the particle size and addition ratio of zircon to reduce glaze defects, make the glaze smooth, soft to the touch, more uniform in light, and have good anti-slip and anti-fouling properties.

[0010] Preferably, the raw material components of the protective glaze slurry include, by weight: 15-19 parts of potassium feldspar, 17-23 parts of sodium feldspar, 2-6 parts of wollastonite, 1-3 parts of calcined talc, 1-3 parts of barium carbonate, 4-8 parts of zinc oxide, 3-5 parts of corundum, 2-6 parts of calcined clay, 5-7 parts of washed clay, 2-4 parts of dolomite, 1-3 parts of aluminum oxide, 10-20 parts of A frit and 13-17 parts of B frit;

[0011] The chemical composition of the A frit is expressed in mass percentage, including: SiO2 43.7%, Al2O3 30.1%, K2O 2.8%, CaO 18.8%, MgO 2% and ZnO 2%, and the remainder is impurities;

[0012] The chemical composition of the B frit is expressed in percentage by mass and includes: SiO2 50.8%, Al2O3 17.6%, K2O 3.0%, Na2O 3.2%, CaO 9.0%, MgO 1.4%, BaO 7.7% and ZnO 5.0%, with the remainder being impurities.

[0013] Preferably, the chemical composition of the protective glaze slurry, measured in mass percentage, includes: SiO2 45% to 55%, Al2O3 15% to 25%, K2O 2% to 5%, Na2O 2% to 6%, CaO 5% to 10%, MgO 1% to 3%, BaO 1% to 4%, ZnO 5% to 10% and loss on ignition 3% to 7%.

[0014] The above protective glaze formula is used in combination with zircon, and the two work synergistically to firmly combine the glaze and the semi-molten zircon, further improving the overall strength.

[0015] On the other hand, the present invention also provides a method for preparing the above-mentioned highly wear-resistant ceramic tile, comprising the following steps:

[0016] (1) According to the raw material formula of the green body layer, the green body is obtained by ball milling, spray granulation, aging and homogenization, pressing and molding, and drying for use;

[0017] (2) preparing the glaze slurry by ball milling according to the glaze layer raw material formula and applying it on the body;

[0018] (3) Inkjet printing a preset pattern on the glaze layer to form a decorative layer;

[0019] (4) Weighing raw materials according to the formula, preparing protective glaze slurry by ball milling, adding zircon to the protective glaze slurry, stirring evenly, and applying it on the decorative layer;

[0020] (5) Sent into the kiln for firing;

[0021] (6) After polishing and waxing, the highly wear-resistant ceramic tile is obtained.

[0022] The ceramic tile prepared by the preparation method provided by the present invention has good performance in many aspects such as wear resistance, anti-slip, touch, light perception and anti-fouling.

[0023] Preferably, in the above preparation method, the specific gravity of the glaze slurry in step (2) is 1.73-1.80 g / mL, and the glaze application amount is 340-380 g / m 2 .

[0024] Preferably, in the above preparation method, the sintering temperature in step (5) is 1200-1260° C., and the sintering period is 50-75 min.

[0025] Preferably, in the above preparation method, the polishing process in step (6) comprises: using 2 + The fiber grinding head polishes the tile surface that has been pre-coated with diamond abrasive liquid, then low-gloss wax is applied to the tile surface, and finally it is dried.

[0026] Preferably, the raw materials of the diamond polishing liquid include, by weight: 4-6 parts of diamond particles, 1-3 parts of dispersant, 0.5-1.5 parts of surfactant, 0.5-1.5 parts of wetting agent, 5-7 parts of pH regulator, 4-6 parts of viscosity regulator, and 75-85 parts of water;

[0027] The particle size of the diamond particles is 400 meshes, the dispersant is water glass, the surfactant is a silane coupling agent, the wetting agent is polyvinyl ether, and the pH regulator is acrylic acid.

[0028] The present invention adopts a grinding and polishing process different from the traditional consolidation polishing, using 2 + Fiber-grinding brush polishing of brick surfaces pre-coated with micron-grade diamond abrasive fluid can avoid the problem of excessive polishing of the brick surface due to the consolidation polishing process, which damages the mullite crystal surface and causes a decrease in wear resistance, while ensuring that the glaze surface has a uniform gloss and a soft touch.

[0029] Compared with the prior art, the present invention has at least the following advantages:

[0030] 1. By physically blending zircon in the protective glaze to improve the glaze strength, the tiles will have higher wear resistance after firing. At the same time, it is ensured that the zircon will not turn white after firing, so that the protective glaze layer still has good light perception and transparency, and does not affect the color of the decorative layer;

[0031] 2. Use appropriate protective glaze formula and zircon to compound and synergize to produce tile glaze with excellent wear resistance, anti-slip, touch, light perception and anti-fouling properties;

[0032] 3. A special grinding and polishing process is used to ensure the wear resistance of the tile surface, while achieving uniform gloss and soft touch of the tile glaze. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be noted that the embodiments in this application and the features in the embodiments can be combined with each other without conflict. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods not mentioned in detail are all process steps or preparation methods known to those skilled in the art.

[0034] The invention discloses a highly wear-resistant ceramic tile, comprising a body layer, a surface glaze layer, a decorative layer and a protective glaze layer. The raw materials for preparing the protective glaze layer include protective glaze slurry and zircon. The particle size of the zircon is 60-120 meshes. Based on the total amount of the protective glaze slurry, the addition ratio of the zircon is 20%-40%.

[0035] Zircon, as a common ceramic raw material, is widely used in the preparation of green bodies and glazes. However, the zirconium silicate contained in zircon usually has a good whitening effect during sintering. Therefore, although zircon has a high hardness, if zircon is used as the only raw material to improve the wear resistance of the glaze after firing, a large amount of zircon needs to be added. The emulsified whitening effect of zircon is not suitable for the transparent protective glaze layer, which will cause the color difference of the decorative layer and the overall whitening of the tile. Therefore, it is difficult to take into account the brightness and transparency of the protective glaze layer when using the hardness of zircon itself to improve the wear resistance of the tile glaze. The present invention adjusts the particle size and addition ratio of zircon particles, and adds zircon to the protective glaze slurry by physical blending, so that the zircon and the protective glaze slurry are well integrated, retaining the crystal form without affecting the transparency of the glaze layer, and the protective glaze is firmly combined with the semi-molten zircon, so that the hardness of the zircon itself gives the tile glaze a higher wear resistance.

[0036] Preferably, the particle size of zircon is 80-100 meshes, and the particle size of zircon is adjusted within a suitable range to avoid the actual anti-slip area after firing being reduced due to excessive particle size, and at the same time reduce the defects such as pricking and poor touch caused by the strong granularity of the glaze surface after firing, so as to improve the anti-slip effect of the glaze surface and have a smooth and soft touch. Preferably, the addition ratio of zircon is 30% based on the total amount of the protective glaze slurry. Adjusting the zircon content so that the zircon protective glaze surface is evenly and appropriately distributed and the zircon particle gap is appropriate is more conducive to improving the anti-fouling performance of the glaze surface.

[0037] In some preferred embodiments, the raw material components of the protective glaze slurry include, by weight: 15-19 parts of potassium feldspar, 17-23 parts of sodium feldspar, 2-6 parts of wollastonite, 1-3 parts of calcined talc, 1-3 parts of barium carbonate, 4-8 parts of zinc oxide, 3-5 parts of corundum, 2-6 parts of calcined clay, 5-7 parts of washed clay, 2-4 parts of dolomite, 1-3 parts of aluminum oxide, 10-20 parts of A frit and 13-17 parts of B frit; wherein the chemical composition of A frit, by weight percentage, includes: SiO2 43.7%, Al2O3 30.1%, K2O 2.8%, CaO 18.8%, MgO 2% and ZnO 2%, and the remainder is impurities; the chemical composition of B frit, by weight percentage, includes: SiO2 50.8%, Al2O3 17.6%, K2O 3.0%, Na2O 3.2%, CaO 9.0%, MgO 1.4%, BaO 7.7% and ZnO 5.0%, and the rest are impurities. A frit and B frit are purchased from Guangdong Pansheng New Material Technology Co., Ltd. The chemical composition of the protective glaze slurry is calculated by mass percentage, including: SiO2 45%~55%, Al2O3 15%~25%, K2O 2%~5%, Na2O 2%~6%, CaO 5%~10%, MgO 1%~3%, BaO 1%~4%, ZnO 5%~10% and loss on burning 3%~7%. By adjusting the protective glaze formula system to match the thermal expansion coefficient of zircon, it is helpful to achieve a good fusion between the glaze and zircon during the firing process, so that the zircon retains the crystal form, further improves the overall strength, and makes the tile surface have a good sense of light and texture, while not affecting the touch and anti-slip performance, and the comprehensive performance is stronger.

[0038] The method for preparing the highly wear-resistant ceramic tile of the present invention comprises the following steps:

[0039] (1) According to the raw material formula of the green body layer, the green body is obtained by ball milling, spray granulation, aging and homogenization, pressing and molding, and drying for use;

[0040] (2) The glaze slurry is prepared by ball milling according to the glaze layer raw material formula and applied to the body. The specific gravity of the glaze slurry is 1.73-1.80 g / mL and the glaze amount is 340-380 g / m 2 ;

[0041] (3) Inkjet printing a preset pattern on the glaze layer to form a decorative layer;

[0042] (4) weighing raw materials according to the formula, preparing protective glaze slurry by ball milling, physically blending zircon with the protective glaze slurry, stirring evenly, and applying on the decorative layer, the particle size of zircon is 60-120 mesh, preferably 80-100 mesh, and the addition ratio of zircon is 20%-40%, preferably, the addition ratio is 30%;

[0043] (5) Send it into the kiln for rapid firing, the firing temperature is 1200-1260°C, and the firing cycle is 50-75 minutes;

[0044] (6) Polishing and waxing: Use 2 + The fiber grinding head polishes the surface of the tile pre-coated with diamond grinding liquid, then applies low gloss wax to the surface of the tile, and finally dries it to obtain the highly wear-resistant tile. The raw materials of the diamond grinding liquid include, by weight: 4 to 6 parts of diamond particles, 1 to 3 parts of dispersant, 0.5 to 1.5 parts of surfactant, 0.5 to 1.5 parts of wetting agent, 5 to 7 parts of pH regulator, 4 to 6 parts of viscosity regulator, and 75 to 85 parts of water; wherein the particle size of the diamond particles is 400 mesh, the dispersant is water glass, the surfactant is a silane coupling agent, such as A-151, etc., the wetting agent is polyvinyl ether, and the pH regulator is acrylic acid. The viscosity regulator can be a known modified cellulose viscosity regulator, such as carboxymethyl cellulose, etc.

[0045] The preparation process provided by the present invention adopts a special grinding and polishing process, which can avoid the problem of reduced wear resistance caused by the traditional consolidation polishing process, which damages the mullite crystal surface and ensures that the glaze has uniform gloss and soft touch. + The fiber grinding heads are purchased from Shuangyi Abrasives Co., Ltd.

[0046] The raw material formula of the body layer of the ceramic tile in the above preparation process can adopt the body layer preparation process and formula known in the art. The raw material formula of the glaze layer can adopt the glaze material formula and preparation process known in the art.

[0047] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only an example within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not intended to be limited to the specific values ​​of the examples below. If the specific conditions are not specified in the examples, proceed according to conventional conditions or the conditions recommended by the manufacturer.

[0048] Exemplarily, the raw material formula of the blank used in the following embodiments includes, by weight: 15 parts of potassium feldspar, 20 parts of sodium feldspar, 20 parts of kaolin, 15 parts of wollastonite, 10 parts of calcined talc, 10 parts of zinc oxide, 2 parts of barium oxide, and 8 parts of quartz; the raw material formula of the glaze slurry used includes, by weight: 25 parts of potassium feldspar, 15 parts of sodium feldspar, 7 parts of dolomite, 20 parts of aluminum oxide, 10 parts of calcined soil, 8 parts of water-washed soil, and 15 parts of quartz. Those skilled in the art should know that other well-known blank formulas and glaze slurry formulas can also be used. The raw material formula of the diamond grinding liquid used in the following embodiments includes, by weight: 5 parts of 400 mesh diamond particles, 2 parts of water glass, 1 part of A-151, 1 part of polyethylene ether, 6 parts of acrylic acid, 5 parts of carboxymethyl cellulose, and 80 parts of water.

[0049] Example 1

[0050] A method for preparing highly wear-resistant ceramic tiles comprises the following steps:

[0051] (1) According to the raw material formula of the green body layer, the green body is obtained by ball milling, spray granulation, aging and homogenization, pressing and molding, and drying for use;

[0052] (2) The glaze slurry is prepared by ball milling according to the glaze layer raw material formula and applied to the body. The specific gravity of the glaze slurry is 1.73 g / mL and the glaze amount is 340 g / m 2 ;

[0053] (3) Inkjet printing a preset pattern on the glaze layer to form a decorative layer;

[0054] (4) Weigh the raw materials according to the formula shown in Table 1, and prepare the protective glaze slurry by ball milling. Physically blend the zircon with the protective glaze slurry, stir evenly, and apply it on the decorative layer. The particle size of the zircon is 80-100 mesh, and the addition ratio of the zircon is 30%. Table 2 shows the chemical composition of the protective glaze slurry;

[0055] (5) Send it into the kiln for rapid firing at a firing temperature of 1200°C and a firing cycle of 50 minutes;

[0056] (6) Polishing and waxing: Use 2 + The fiber grinding head polishes the surface of the tile pre-coated with diamond grinding liquid, then applies low-gloss wax to the surface of the tile, and finally dries it to obtain the highly wear-resistant tile.

[0057] Example 2

[0058] A method for preparing highly wear-resistant ceramic tiles comprises the following steps:

[0059] (1) According to the raw material formula of the green body layer, the green body is obtained by ball milling, spray granulation, aging and homogenization, pressing and molding, and drying for use;

[0060] (2) The glaze slurry is prepared by ball milling according to the glaze layer raw material formula and applied to the body. The specific gravity of the glaze slurry is 1.76 g / mL and the glaze amount is 360 g / m 2 ;

[0061] (3) Inkjet printing a preset pattern on the glaze layer to form a decorative layer;

[0062] (4) Weigh the raw materials according to the formula shown in Table 1, and prepare the protective glaze slurry by ball milling. Physically blend the zircon with the protective glaze slurry, stir evenly, and apply it on the decorative layer. The particle size of the zircon is 80-100 mesh, and the addition ratio of the zircon is 30%. Table 2 shows the chemical composition of the protective glaze slurry;

[0063] (5) Send it into the kiln for rapid firing, the firing temperature is 1230℃, and the firing cycle is 65min;

[0064] (6) Polishing and waxing: Use 2 + The fiber grinding head polishes the surface of the tile pre-coated with diamond grinding liquid, then applies low-gloss wax to the surface of the tile, and finally dries it to obtain the highly wear-resistant tile.

[0065] Example 3

[0066] A method for preparing highly wear-resistant ceramic tiles comprises the following steps:

[0067] (1) According to the raw material formula of the green body layer, the green body is obtained by ball milling, spray granulation, aging and homogenization, pressing and molding, and drying for use;

[0068] (2) The glaze slurry is prepared by ball milling according to the glaze layer raw material formula and applied to the body. The specific gravity of the glaze slurry is 1.80 g / mL and the glaze amount is 380 g / m 2 ;

[0069] (3) Inkjet printing a preset pattern on the glaze layer to form a decorative layer;

[0070] (4) Weigh the raw materials according to the formula shown in Table 1, and prepare the protective glaze slurry by ball milling. Physically blend the zircon with the protective glaze slurry, stir evenly, and apply it on the decorative layer. The particle size of the zircon is 80-100 mesh, and the addition ratio of the zircon is 30%. Table 2 shows the chemical composition of the protective glaze slurry;

[0071] (5) Send it into the kiln for rapid firing, the firing temperature is 1260℃, and the firing cycle is 75min;

[0072] (6) Polishing and waxing: Use 2 +The fiber grinding head polishes the surface of the tile pre-coated with diamond grinding liquid, then applies low-gloss wax to the surface of the tile, and finally dries it to obtain the highly wear-resistant tile.

[0073] Table 1 Raw material composition of protective glaze slurry (parts by weight)

[0074]

[0075] Table 2 Chemical composition of protective glaze slurry (%)

[0076]

[0077] Example 4

[0078] This example adopts the same preparation process and parameters as Example 2, except that the addition ratio of zircon is 20%.

[0079] Example 5

[0080] This example adopts the same preparation process and parameters as Example 2, except that the addition ratio of zircon is 40%.

[0081] Example 6

[0082] This example adopts the same preparation process and parameters as Example 2, except that the particle size of zircon is 60-80 mesh.

[0083] Example 7

[0084] This example uses the same preparation process and parameters as Example 2, except that the particle size of the zircon is 100-120 meshes.

[0085] Example 8

[0086] This embodiment adopts the same preparation process and parameters as those of Embodiment 2, except that the protective glaze slurry adopts the formula components (parts by weight) shown in the following table.

[0087]

[0088] Comparative Example 1

[0089] This comparative example adopts the same preparation process and parameters as Example 2, except that zircon is not added to the raw materials for the protective glaze layer.

[0090] Comparative Example 2

[0091] This comparative example adopts the same preparation process and parameters as Example 2, except that the zircon added to the protective glaze layer raw material is replaced by corundum, the particle size of the corundum is 80-100 mesh, and the addition ratio is 30%.

[0092] Comparative Example 3

[0093] This comparative example adopts the same preparation process and parameters as Example 2, except that the particle size of zircon is less than 60 mesh.

[0094] Comparative Example 4

[0095] This comparative example adopts the same preparation process and parameters as Example 2, except that the particle size of zircon is larger than 120 mesh.

[0096] Comparative Example 5

[0097] This comparative example adopts the same preparation process and parameters as Example 2, except that the addition ratio of zircon is 50%.

[0098] Comparative Example 6

[0099] This comparative example adopts the same preparation process and parameters as Example 2, except that the grinding and polishing process adopts traditional consolidated polishing.

[0100] The performance parameters of the high wear-resistant tiles prepared in Examples 1 to 8 and Comparative Examples 1 to 6 were tested, and the testing standards and methods were as follows:

[0101] 1. Wear resistance: GB / T 3810.7-2016 is used to test the wear resistance: the wear of the brick surface after grinding at a specific grinding number of revolutions is observed, and it is divided into 0-5 levels, among which, the visible wear after 100 revolutions is level 0, the visible wear after 150 revolutions is level 1, the visible wear after 600 revolutions is level 2, the visible wear after 750 / 1500 revolutions is level 3, the visible wear after 2100 / 6000 / 12000 revolutions is level 4, and the visible wear after more than 12000 revolutions is level 5.

[0102] 2. Antifouling: Refer to the national standard GB / T 3810.14-2016 to test the antifouling performance: The antifouling performance of the brick surface treated with the surface treatment agent is tested. The test principle is to bring the pollutant (chrome green, iodine tincture and olive oil, etc.) into contact with the front of the brick and let it act for a certain period of time, then clean the brick surface according to the prescribed cleaning method, observe the changes on the brick surface to determine the brick's pollution resistance, the grades are divided into 1-5, and grade 5 has the best pollution resistance.

[0103] 3. Anti-slip performance: The anti-slip performance is tested in accordance with the national standard GB / T 37798-2019. The slope method (wearing shoes and applying oil) is used to test the anti-slip performance of the tile surface. The grades are marked as "-, R9, R10, R11, R12, R13". Among them, R12-R13 has high anti-slip performance, R10-R11 has medium anti-slip performance, and R9 and below have low anti-slip performance.

[0104] 4. Surface effect: judged by human touch (sliding your palm flat on the brick surface), and using a gloss meter to measure the glossiness of different positions on the brick surface.

[0105] 5. Mohs hardness: The hardness of a brick is determined by scratching the brick surface with a group of minerals with gradually increasing hardness (such as gypsum, calcite, fluorite, diamond, etc.) and observing the wear of the brick surface, starting from gypsum (Mohs hardness level 1) and gradually increasing to diamond (Mohs hardness level 10).

[0106] The test results are shown in Table 3.

[0107] Table 3

[0108]

[0109] As shown in Table 3, the tiles prepared in Examples 1 to 8 are physically blended with zircon in the protective glaze slurry, while no zircon is added in Comparative Example 1. The wear resistance of the tiles in Examples 1 to 8 is significantly improved compared with that in Comparative Example 1. In Comparative Example 2, corundum is used to replace zircon, which requires a higher firing temperature to melt it, resulting in excessive production capacity consumption, and the particles that are not easy to burn have poor bonding with the glaze, resulting in reduced wear resistance. The glaze surface is rough and white after firing, affecting the color development of the decorative layer. The zircon particles added in Comparative Example 3 are too large in size, which will cause defects such as whitening that is not easy to burn during the firing process, reduced actual anti-slip area, and poor touch. The larger particles have poor fusion with the glaze during the firing process, are prone to falling off, and have reduced wear resistance. In addition, the subsequent grinding and polishing effect is affected, causing the problem of uneven light perception. The zircon particles added in Comparative Example 4 are too small in size, and most of the glaze surface is melted flat, with poor wear resistance, anti-slip and anti-fouling properties. In Comparative Example 5, the proportion of zircon added is too high, which will cause the problem of easy dirt hiding on the tile surface due to the small gap between particles, and the excessive zircon will affect the poor integration between the glaze during the firing process, which is easy to cause shedding, affecting the wear resistance, and the glaze surface is rough and white after firing. Comparative Example 6 adopts the traditional consolidation polishing process, which damages the mullite crystal surface on the glaze layer and significantly reduces the surface hardness of the tile.

[0110] By comparing Example 1 with Examples 4 to 7, it can be seen that when the particle size of the zircon particles is 80 to 100 mesh and the addition ratio is 30%, the wear resistance, anti-slip properties, anti-fouling properties and surface effects of the tile surface can be better balanced, and high-wear-resistant tiles with the best comprehensive performance can be obtained.

[0111] Comparing Example 2 and Example 8, the ceramic tiles made with ordinary protective glaze slurry are prone to interface loosening during annealing and a small amount of whitening occurs due to the mismatch in expansion coefficients between the ordinary protective glaze and zircon. This indicates that the protective glaze slurry formula described in the present invention is compounded with zircon to achieve synergistic effects and the resulting ceramic tiles have better surface performance.

[0112] In summary, by adopting the scheme described in the present invention to physically blend zircon in the protective glaze slurry, and adjusting the particle size and addition ratio of zircon within a suitable range, the purpose of improving the wear resistance of the tile surface can be achieved, and at the same time, the glaze surface is not affected by the emulsification and whitening of zircon after firing. In particular, by adopting the protective glaze slurry formula described in the present invention, the two work synergistically, and the glaze surface after firing has wear resistance, high transparency, anti-slip and anti-fouling properties. By adjusting the specific parameters, when the particle size of zircon is between 80 and 100 mesh and the addition ratio is 30%, the comprehensive performance of the fired tile is the best.

[0113] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A highly wear-resistant ceramic tile, characterized in that: The high wear-resistant ceramic tile is composed of a body layer, a surface glaze layer, a decorative layer and a protective glaze layer. The raw materials for preparing the protective glaze layer are composed of a protective glaze slurry and zircon. The particle size of the zircon is 60-120 meshes. Based on the total amount of the protective glaze slurry, the addition ratio of the zircon is 20%-40%; The raw material components of the protective glaze slurry are composed, by weight, of 15 to 19 parts of potassium feldspar, 17 to 23 parts of sodium feldspar, 2 to 6 parts of wollastonite, 1 to 3 parts of calcined talc, 1 to 3 parts of barium carbonate, 4 to 8 parts of zinc oxide, 3 to 5 parts of corundum, 2 to 6 parts of calcined clay, 5 to 7 parts of washed clay, 2 to 4 parts of dolomite, 1 to 3 parts of aluminum oxide, 10 to 20 parts of A frit and 13 to 17 parts of B frit; The chemical composition of the A frit is expressed in mass percentage, including: SiO2 43.7%, Al2O3 30.1%, K2O2.8%, CaO 18.8%, MgO 2% and ZnO 2%, and the remainder is impurities; The chemical composition of the B frit is expressed in percentage by mass, including: SiO2 50.8%, Al2O3 17.6%, K2O 3.0%, Na2O3.2%, CaO 9.0%, MgO 1.4%, BaO 7.7% and ZnO 5.0%, with the remainder being impurities; The method for preparing the highly wear-resistant ceramic tile comprises the following steps: (1) According to the raw material formula of the green body layer, the green body is obtained by ball milling, spray granulation, aging and homogenization, pressing and molding, and drying for use; (2) preparing the glaze slurry by ball milling according to the glaze layer raw material formula and applying it on the body; (3) Inkjet printing a preset pattern on the glaze layer to form a decorative layer; (4) Weighing raw materials according to the formula, preparing protective glaze slurry by ball milling, adding zircon to the protective glaze slurry, stirring evenly, and applying it on the decorative layer; (5) Sent into the kiln for firing; (6) After polishing and waxing, the highly wear-resistant ceramic tile is obtained; The polishing process in step (6) includes: using 2 + The fiber grinding head polishes the tile surface that has been pre-coated with diamond abrasive liquid, then low-gloss wax is applied to the tile surface, and finally it is dried.

2. A highly wear-resistant ceramic tile as claimed in claim 1, characterized in that: The particle size of the zircon is 80-100 meshes.

3. A highly wear-resistant ceramic tile as claimed in claim 1, characterized in that: Based on the total amount of the protective glaze slurry, the addition ratio of the zircon is 30%.

4. A highly wear-resistant ceramic tile as claimed in claim 1, characterized in that: The chemical composition of the protective glaze slurry, measured in percentage by mass, includes: SiO2 45% to 55%, Al2O3 15% to 25%, K2O 2% to 5%, Na2O 2% to 6%, CaO 5% to 10%, MgO 1% to 3%, BaO 1% to 4%, ZnO 5% to 10% and loss on ignition 3% to 7%.

5. The method for preparing a highly wear-resistant ceramic tile according to any one of claims 1 to 4, characterized in that: The steps include: (1) According to the raw material formula of the green body layer, the green body is obtained by ball milling, spray granulation, aging and homogenization, pressing and molding, and drying for use; (2) preparing the glaze slurry by ball milling according to the glaze layer raw material formula and applying it on the body; (3) Inkjet printing a preset pattern on the glaze layer to form a decorative layer; (4) Weighing raw materials according to the formula, preparing protective glaze slurry by ball milling, adding zircon to the protective glaze slurry, stirring evenly, and applying it on the decorative layer; (5) Sent into the kiln for firing; (6) After polishing and waxing, the highly wear-resistant ceramic tile is obtained; The polishing process in step (6) includes: using 2 + The fiber grinding head polishes the tile surface that has been pre-coated with diamond abrasive liquid, then low-gloss wax is applied to the tile surface, and finally it is dried.

6. The preparation method according to claim 5, characterized in that: The specific gravity of the glaze slurry in step (2) is 1.73-1.80 g / mL, and the glaze application amount is 340-380 g / m 2 .

7. The preparation method according to claim 5, characterized in that: The firing temperature in step (5) is 1200-1260° C., and the firing period is 50-75 min.

8. The preparation method according to claim 5, characterized in that: The raw materials of the diamond polishing liquid include, by weight: 4-6 parts of diamond particles, 1-3 parts of dispersant, 0.5-1.5 parts of surfactant, 0.5-1.5 parts of wetting agent, 5-7 parts of pH regulator, 4-6 parts of viscosity regulator, and 75-85 parts of water; The particle size of the diamond particles is 400 meshes, the dispersant is water glass, the surfactant is a silane coupling agent, the wetting agent is polyvinyl ether, and the pH regulator is acrylic acid.

Citation Information

Patent Citations

  • Flash super-wear-resistant diamond glaze, ceramic tile and preparation method thereof

    CN113429130A